Themiksen temppeli : vanhan Vaasan hovioikeudentalo Kustaa III:n valistuspyrkimysten monumentti - Harju, Virpi (1997)
The subject of the research is the Old Vaasa Court of Appeal building (completed in 1786), designed by the Swedish architect Carl Fredrik Adelcrantz (1716-1796). The Court of Appeal building represents the French architectural ideals embraced by Gustav III and with which Adelcrantz was familiar, too. It can be considered a Swedish example of Louis XV classicism. The main objective of the research is to reveal the exceptionally representative status of the Court of Appeal building and also to analyse briefly why no proper court-house tradition has developed in Finland. The research also examines the Court of Appeal and the Court of Appeal building, particularly the symbolism and iconography of the court's insignia, with the aim of clarifying the origin and meaning of the emblems on a relief preserved from the building and their status in comparison with other visual representations of justice. The research is to a large extent antiquarian. A historical, descriptive and comparative method is used in the work. Using comparisons from legal history, for example, an attempt is made to analyse the subject's similarities in terms of judicial function with other corresponding court buildings in Sweden-Finland. An iconographical and iconological method is applied in research relating to symbolism and iconography. Gustav III established the Vaasa Court of Appeal in summer 1775 in order to improve the administration of law and he also initiated a project to build a dedicated building for the superior court of justice. Adelcrantz prepared the plans and a cost estimate for the Court of Appeal building. Gustav III also made a significant contribution to the design of the building. In addition, Adelcrantz drew up a town plan for the district where the court building was erected, probably using as a model the Place de Stanislaw Leszczynski, designed in the 1750s by Emmanuel Here de Corny for the city of Nancy in France. The arrangement of the rooms of the Court of Appeal building follows French examples, most probably the designs of Charles-Etienne Briseux. A comparison of Court of Appeal buildings in Sweden-Finland revealed that layouts and floor divisions of the Court of Appeal buildings of Svea, Turku, Gota and Vaasa were not similar. Nevertheless, the functions of the rooms were broadly the same. In the general design of the prominent central section of the main fac;ade, Adelcrantz had very clearly approached the designs of the French architectural theoretician Jean-Frarn;ois de Neufforge. On the exterior, typical rococo features are most visible in the wings, which have many points in common with the architecture of Carl Harleman. A comparison of the exteriors of Court of Appeal buildings in Sweden-Finland revealed no similarities and connecting features which might be characteristic of court buildings. Clean, unassuming lines dominated the Court of Appeal building's fixed Gustavian furnishings. The courtroom's impressive ornamentation differed from the furnishings of the other rooms, which also appeared in other Court of Appeal buildings throughout the kingdom; it was a question of the hierarchical grading of the rooms. The Court of Appeal building experienced its greatest change after the Fire of Vaasa in 1852, when the building was converted into the Church of Mustasaari (1863). A new Court of Appeal building (completed in 1862), designed by the province architect Carl Axel Setterberg, provided an excellent setting to preserve the Court of Appeal's cultural and historical tradition and its valuable collection of objects. The founding of the Court of Appeal and the Court of Appeal building can be considered as important symbols representing Gustav Ill's social and personal outlook. The architecture of the Court of Appeal building was influenced by the idea of a temple of justice. The development of the administration of justice, which was one of the king's enlightenment measures, is particularly well illustrated by an iconographically important relief (1786) preserved from the Court of Appeal building. It depicts all the most common symbols of justice: scales, blindfold, fasces and axe, and sword. The symbols are linked to classical mythology. Other similar presentations of the symbols of justice have not be encountered elsewhere in Finland. The architecture of court buildings was determined in different countries by the prevailing traditions and legal systems. The administration of justice in Finland has remained in this respect rather democratic. Up to recent times court buildings have been quite primitive compared to their counterparts in the old established countries of Western Europe. It was not until the city courts were organised on a national basis that a period of court-house construction began in the 1970s. In Finland there has been no tradition of depicting law and justice in objects or pictures. A clear exception among Finland's court buildings is Gustav Ill's Old Vaasa Court of Appeal, which is distinguished by its architectural magnificence and its iconographical importance. It also stands apart from the kingdom of Sweden-Finland's other Court of Appeal buildings. The Old Vaasa Court of Appeal building expressed very clearly the stylistic ambitions of Adelcrantz's architecture and it has been considered one of the most important secular buildings from his peak period. The building expresses, perhaps for the first time in Finland, the tectonically and orthodoxly designed Tuscan order, while at the same time being the principal monument to Louis XV classicism in Finland. The building is part of the European court-house tradition.